Comprehension of Standard English text and digital textism during childhood - Johnson, Genevieve (Australia Asia Research and Education Foundation, 2012)
In contrast to teacher reports, recent research suggests that use of textese (i.e., idiosyncratic written conventions used in text messaging) is positively associated with Standard English literacy skills during childhood. The current investigation reduces confounds by asking children to respond to traditional reading test items and define common textisms in equivalent formats under identical conditions. Ninety-one children in grades 3 through 6 translated five common abbreviations used in text messaging and, under identical conditions, completed two measures of Standard English literacy. Without exception and despite small numbers, children who correctly defined textisms demonstrated superior skills in reading fluency and sentence comprehension (i.e., reading speed and response indicating comprehension) than children unable to define the common texting terms. Such results add to the growing number of studies that conclude a positive association, if not effect, between digitalk and traditional literacy across the life span.